2021
DOI: 10.1177/0890334421993467
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Lactation Care is Associated With Improved Outcomes in a Referral NICU

Abstract: Background Mother’s milk improves outcomes. Referral neonatal intensive care units face unique lactation challenges with maternal–infant separation and maternal pump dependency. Little is known about lactation resource allocation in this high-risk population. Research Aims To determine differences in human milk outcomes, (1) the proportion of infants fed exclusive or any mother’s milk and (2) recorded number and volume of pumped mothers’ milk bottles, between two models of lactation care in a referral neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…While practices such as expressing milk within one hour of birth and kangaroo care may depend on the individual clinical context, they also require more active professional support, relying on staff time and availability, technical skill and competency of nurses and lactation support providers, and staff and patient buy-in. Studies have found that increasing the number of staff whose roles are fully dedicated to providing lactation support improves breastfeeding outcomes (25); similarly, adequate nurse sta ng ratios and nursing staff with higher levels of education are also associated with higher rates of infants with VLBW receiving human milk at discharge (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While practices such as expressing milk within one hour of birth and kangaroo care may depend on the individual clinical context, they also require more active professional support, relying on staff time and availability, technical skill and competency of nurses and lactation support providers, and staff and patient buy-in. Studies have found that increasing the number of staff whose roles are fully dedicated to providing lactation support improves breastfeeding outcomes (25); similarly, adequate nurse sta ng ratios and nursing staff with higher levels of education are also associated with higher rates of infants with VLBW receiving human milk at discharge (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although medical complications can make these practices more challenging for families whose infants require advanced neonatal care, hospital practices and policies can facilitate and support lactation management. Providing families with proactive lactation support in the NICU setting that includes education on the importance of providing mother's own milk and the recommended frequency of pumping has been found to improve the likelihood of infants receiving their mother's own milk while in the NICU (25).…”
Section: Introductionmentioning
confidence: 99%